2009
DOI: 10.1111/j.1462-2920.2009.02060.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structure in autotrophic nitrifying granules characterized by experimental and simulation analyses

Abstract: This study evaluates the community structure in nitrifying granules (average diameter of 1600 mum) produced in an aerobic reactor fed with ammonia as the sole energy source by a multivalent approach combining molecular techniques, microelectrode measurements and mathematical modelling. Fluorescence in situ hybridization revealed that ammonia-oxidizing bacteria dominated within the first 200 mum below the granule surface, nitrite-oxidizing bacteria a deeper layer between 200 and 300 mum, while heterotrophic bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 65 publications
7
63
0
Order By: Relevance
“…In general, members of the genus Nitrosospira and the N. oligotropha clusters prevail in environments with low ammonia concentrations (Bollmann and Laanbroek 2001;Limpiyakorn et al 2005;Otawa et al 2006;Wang et al 2010), whereas environments rich in ammonia are dominated by members of the N. europaea-N. eutropha clusters (Logemann et al 1998;Limpiyakorn et al 2005;Tan et al 2008). Hence, the finding that the dominant AOB in the investigated nitrifying reactors belonged to the N. europaea lineage is not surprising and corresponds to what was observed before (Logemann et al 1998;Tan et al 2008;Matsumoto et al 2010). However, the peculiar morphology has no analogues among the so far described pure cultures of this AOB genus despite of being a well-documented phenomenon in the wastewater treatment plants and bioreactors.…”
Section: Discussionsupporting
confidence: 52%
“…In general, members of the genus Nitrosospira and the N. oligotropha clusters prevail in environments with low ammonia concentrations (Bollmann and Laanbroek 2001;Limpiyakorn et al 2005;Otawa et al 2006;Wang et al 2010), whereas environments rich in ammonia are dominated by members of the N. europaea-N. eutropha clusters (Logemann et al 1998;Limpiyakorn et al 2005;Tan et al 2008). Hence, the finding that the dominant AOB in the investigated nitrifying reactors belonged to the N. europaea lineage is not surprising and corresponds to what was observed before (Logemann et al 1998;Tan et al 2008;Matsumoto et al 2010). However, the peculiar morphology has no analogues among the so far described pure cultures of this AOB genus despite of being a well-documented phenomenon in the wastewater treatment plants and bioreactors.…”
Section: Discussionsupporting
confidence: 52%
“…They were detected in wastewater treatment systems from different industries as well as in activated sludge systems in municipal WWTPs [21,22] and also in autotrophic nitrifying granules [23]. In the present study they appear almost in constant amounts in the reactors fed with synthetic media and fish cannery wastewater.…”
Section: Inoculum and Wastewater Compositionmentioning
confidence: 51%
“…5A). It has been reported that dissolved oxygen penetrates various nitrifying biofilms approximately 50-200 µm from the surface (17,27,31,38). It is therefore likely that the full penetration of the nascent granules by oxygen resulted in a uniform distribution of N. mobilis.…”
Section: Discussionmentioning
confidence: 99%
“…Matsumoto et al (27) reported that the inside of nitrifying granules 1.6 mm in diameter is anoxic and mainly occupied by heterotophic bacteria. The report concluded that the heterotophic bacteria conduct denitrification inside the nitrifying granules.…”
Section: No2mentioning
confidence: 99%
See 1 more Smart Citation